A perspective on challenges and opportunities in developing high entropy-ultra high temperature ceramics. Issue 16 (November 2020) - Nisar, Ambreen; Zhang, Cheng; Boesl, Benjamin; Agarwal, Arvind
Abstract: The emergence of a new class of high entropy ultra-high temperature ceramics (HE-UHTCs) is expected to possess exceptionally superior mechanical, oxidation, and erosion resistance as compared to conventional UHTCs. The improvement in the properties of HE-UHTCs is attributed to the high configurational entropy of the multi-component system stabilized into a single-phase, but with little discussion on entropy contributions. This perspective article presents a viewpoint on the critical scientific question regarding the actual role entropy plays in stabilizing and enhancing the thermo-mechanical properties of a multi-component system. The high throughput first-principle calculations, which can provide the entropy formation ability (EFA) of thermodynamically stable HE-UHTCs, can prove to be valuable toolset to this puzzle. HE-UHTCs show enhancement in the mechanical properties much higher than the predicted rule of the mixture, which cannot traditionally be explained by a mere solid solution formation effect. Isothermal oxidation studies of HE-UHTCs limited to furnace testing state remarkable oxidation resistance which is attributed to the passivity of complex, layered structure, and composition of the oxide scale. However, whether all the constituents in the HE-UHTC system react simultaneously or preferential oxidation takes place needs to be addressed. To address all these issues, an integrated computational and experimental approach has been postulated towards designing a thermal protection system (TPS) for re-entry applications. Succeeding the approach will provide new opportunities in the compositional space of HE-UHTCs with tailored properties.